2021
DOI: 10.1186/s12879-021-05975-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcome of influenza virus infection among adults hospitalized with severe COVID-19: a retrospective cohort study from Wuhan, China

Abstract: Background Coronavirus disease 2019 (COVID-19) is an emerging infectious disease that rapidly spreads worldwide and co-infection of COVID-19 and influenza may occur in some cases. We aimed to describe clinical features and outcomes of severe COVID-19 patients with co-infection of influenza virus. Methods Retrospective cohort study was performed and a total of 140 patients with severe COVID-19 were enrolled in designated wards of Sino-French New Cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
(20 reference statements)
1
7
0
Order By: Relevance
“…After excluding low-quality studies, a similar meta-estimate was observed (Figure S2, panel B in the Online Supplementary Document ). Results from two high-quality studies [ 19 , 25 ] using multivariable models were consistent with our meta-estimates although another high-quality study [ 17 ] showed no significant difference in receiving mechanical ventilation between the two groups.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…After excluding low-quality studies, a similar meta-estimate was observed (Figure S2, panel B in the Online Supplementary Document ). Results from two high-quality studies [ 19 , 25 ] using multivariable models were consistent with our meta-estimates although another high-quality study [ 17 ] showed no significant difference in receiving mechanical ventilation between the two groups.…”
Section: Resultssupporting
confidence: 87%
“…The total number of SARS-CoV-2 patients co-infected with influenza/RSV and mono-infected patients per study ranged from 22 to 4501. Nine studies were mainly conducted in Asia, six of which were from China [ 16 , 17 , 21 - 23 , 25 ]. For viral detection method, SARS-CoV-2 was detected using PCR for all studies whereas influenza and / or RSV co-infection was confirmed by PCR, serological testing, or antigen assays.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 10 Of the few reports, some suggest no difference in the clinical course of dually infected patients compared with those infected with SARS‐CoV‐2 alone; however, both improved and worse outcomes have been reported. 11 , 12 , 13 , 14 From a clinical and public health perspective, the burden on healthcare systems due to epidemics of either virus alone, let alone overlapping epidemics, remains a credible threat. Thus, without intervention, the potential of a ‘syndemic’—a term coined to describe twin synergistic epidemics—due to the cocirculation of influenza and COVID‐19 is a serious reality, especially as public health and social measures are relaxed.…”
mentioning
confidence: 99%